CHANGE MANAGEMENT IN THE IMPLEMENTATION OF FORMAL DINIYAH EDUCATION PROGRAM AT AL-HIKMAH ISLAMIC BOARDING SCHOOL, BANDAR LAMPUNG - Dirgatama, Erwanda; Fitryansyah, Allya; Ilhami, Ilhami; Elice, Deti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The main process in achieving success in the management of educational institutions is highly dependent on change management and its supporting components. In the change management at Al-Hikmah Islamic Boarding School in Bandar Lampung, an overview of the implementation of the Formal Diniyah Education Program is presented. This program is rooted in the Kitab Kuning, which are classical Islamic texts that serve as references for the tradition of Islamic scholarship in pesantren. In line with the pesantren's motto, which aims to produce students who are qualified as true scholars (Ulama Sejati), this research aims to explore how change management is implemented at Al-Hikmah Islamic Boarding School in Bandar Lampung. The researcher employed data collection techniques such as observation, interviews, and documentation. For data validity, the research used source triangulation. The data analysis involved data reduction, data presentation, and drawing conclusions. The findings of this study show that change management at Al-Hikmah Islamic Boarding School includes the following phases: Exploration Phase, This phase involves an analysis of aspects that support the Formal Diniyah Education Program (PDF), such as resource needs, government policies, and local community perspectives. Planning Phase, This phase is crucial in change management, where the pesantren leader must develop clear strategies and plans for the implementation of the Formal Diniyah Education Program. Action Phase, In this phase, effective teaching and learning activities are carried out, educational facilities are developed, and strict quality control is enforced. Additionally, the pesantren leadership ensures that the Formal Diniyah Education Program runs smoothly even without permanent donors. Integration Phase, This phase represents the final step in the change management process. Furthermore, the study aims to ensure that the Formal Diniyah Education Program produces high-quality future scholars (ulama).